Study of Effective Components on Guidance plan Improvement base of Attitude of Rural Managers and Rural Council Members in Central district of Kermanshah County (تحقیقات کاربردی علوم جغرافیایی)
Guidance plan does with economic, structure, social and cultural attitude in Iran and this plan has high effect on rural life. Therefore it is essential that we study guidance plan base of rural managers and rural councils attitude. Investigative method was descriptive, analysis (survey method) and research tools were questionnaire. Statistical society includes rural managers and rural council members. Sampling method in rural managers was census method and rural council methods were random sampling method. Number of rural managers was 31 and number of rural council members was 103 respondents (in councils with 3 members we select 3 respondents and in rural councils with 5 members we select 3 respondents). Results shows that guidance plan have positive effect on structure of village. But in economic and cultural dimensions, there is no effect on villages. Maps of guidance plan were weak. Respondent believe that there are low satisfaction about guidance plan among rural managers and rural council members. It is important and we must notice to it.